Community Dynamics of Tanjung Obit Village, the Bacan Island, South Halmahera: a Social Resilience Perspective - Kharirotul Suhaila; Suherman Suherman (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Tanjung Obit Village is one of the villages in Bacan Island, South Halmahera. Recently, Tanjung Obit has socially and economically is developing rapidly because its main economic activities are driven by gold and bacan stone mines. Besides this, Tanjung Obit Village has the potential of natural resources in the form of plantations and fisheries which are very abundant. Mining activities and natural resource management activities affect people’s lives there, especially in terms of the economic aspect. The study aimed to understand and analyze the social resilience of the community. The data collection was conducted through interviewing community leaders, asking the village residents to complete a questionnaire and field observations of the village. The findings of the study showed that in their daily life, people had maintained their social and social resiliencies. In terms of the economic aspect, the optimization of natural resources potentials was very important to improve their social welfare. In addition, by implementing the four aspects of social resiliencies comprising mimicking, adaptive, and transformative capacities as well as local wisdom, Tanjung Obit’s people had survived and been capable of developing themselves further in the future.